Tratamento de água oleosa mediante processo de eletrofloculação com eletrodos de alumínio a partir de materiais reciclados - Silva, Italo Vidal da (2023)
Water is one of the most important natural assets for the maintenance of life on the planet and for the balance of its ecosystem, in such a way that allows the maintenance and development of society since ancient times. Over the decades and with the exponential development of society, the scientific field, and especially the industrial sector, which directly impacted the reduction of various natural resources, bringing to light that the unbridled and unsystematic use of these resources would severely impact not only the planet, but also the life and development of the various fields, especially the oil industry, which generates a large volume of oily effluents, also known as produced petroleum water. Given the growing global concern about the water crisis, it is necessary to implement political measures and environmental awareness, for the quality of water, and to develop alternatives for the treatment of affluents and effluents, such as electroflocculation with the use of recycled materials. Thus, the objective of this work was to analyze the efficiency of the treatment for electroflocculation using electrodes produced from recycled aluminum cans for the treatment of synthetic oily effluent, evaluating the percentage of removal from the parameters of the samples before and after treatment by electrolytic means, according to the following physicalchemical analyses: oil and grease content (O&G), total alkalinity, chlorides, total hardness, pH, turbidity and chemical oxygen demand (COD). The experiments were performed on a laboratory scale, at voltages of 5 and 12 volts and a continuous current of 1.5 amperes from an electrolytic cell and aluminum electrodes from recyclable cans. The tests were performed in a 2.5 L volume, lasting 30 minutes, with tests under external agitation. Through the analyses the efficiency in the removal of impurities was verified. The physicochemical parameters were close in removal efficiency for the tensions of 5 volts and 12 volts, respecrively, for O&G (98.10% and 99.68%), total alkalinity (12.50% and 17.50%), chlorides (2.56% and 4.64%), total hardness (14.29% and 7.14%), pH (7.17 and 7.27), turbidity (84.31% and 99.84%) and COD (38.97% and 54.74%), the cost for the processes (R$ 1.92/m3 (US$ 0.37/m3) and R$ 4.12/m3 (US$ 0.79/m3)), respectively. The proposal of electroflocculation with alternative materials (recycled) proved to be an effective alternative in the treatment of oily wastewater, managing to fit the restrictive parameters for discharge of effluents into water bodies.